Description of the pupa and male of Paryphoconus grandis Macfie (Diptera: Ceratopogonidae) - Ronderos, María M.; Marino, Pablo I.; Díaz, Florentina (Zootaxa, 2012)
The pupa and male of Paryphoconus grandis Macfie are described for the first time. Pupae were collected from the edgeof a stream margin in Corrientes province, Argentina and reared to adults. Pupae and adults are illustrated and photographed. The species is known from Mexico to northern Argentina.